2004
DOI: 10.9744/kata.2.1.40-43
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Work in the Prewriting Stage

Abstract: This paper explores the notion of collaborative work in the prewriting stage. Several collaborative prewriting activities are presented to encourage students to optimize their peers' help in obtaining ideas to write. Those activities will ultimately help students get interesting ideas to write and develop them into dynamic writing. Keywords: collaborative work, prewriting, dynamic writing, brainstorming, chained information, clustering, trategic questioning, information gathering, buddy journals Helping st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Sharing her classroom experience in dynamic writing, Wijaya (2000) argues that that collaborative activities are useful to help learners generate ideas in prewriting process. Dheram (1995) found that learners made revisions following feedback both in form and in content.…”
Section: Pedagogical Concerns Of Process Orientationmentioning
confidence: 99%
“…Sharing her classroom experience in dynamic writing, Wijaya (2000) argues that that collaborative activities are useful to help learners generate ideas in prewriting process. Dheram (1995) found that learners made revisions following feedback both in form and in content.…”
Section: Pedagogical Concerns Of Process Orientationmentioning
confidence: 99%
“…But palm oil has some disadvantages between being easily oxidized and being damaged because palm oil contains lots of fatty acids. The use of palm oil will disrupt the availability of palm oil as cooking oil so as to interfere with food security [7]. In addition, biodiesel production from vegetable oil is higher than fossil oil due to high raw material cost.…”
Section: Introductionmentioning
confidence: 99%